Metachronous Basal Cell Carcinoma and Primary Plasmacytic Leukemia Associated With Dermatomyositis - Yuan YANG,; Qibing XIE,; Geng YIN, (Archives of Rheumatology, 2014)
Dermatomyositis is associated with cancer frequently. However, successive occurrence of two malignancies in one person is rare. In this article, we present a 71-year-old female patient who was diagnosed as dermatomyositis based on skin lesions, muscle weakness, elevated muscle enzymes, electromyography, and muscle biopsy. Two years later, the patient had an ulcer on the left nasolabial groove. A resection was performed after basal cell carcinoma was confirmed by tissue biopsy. Two years after resection, serum M protein, urinary l light chain, and neoplastic plasma cells infiltration in bone marrow biopsy of the patient were evaluated. Findings were compatible with the plasmacytic leukemia. Dermatomyositis patients may suffer from multiple tumors due to carcinogenic susceptibility. Therefore, physicians should continue to monitor dermatomyositis patients after the occurrence of the first tumor since they still have the possibility of developing another malignancy.